Supra Continuous g in Topological Spaces - S. Usharani (International Journal of Mathematics And its Applications, 2018)
The aim of this paper is to introduce and investigate a new class of sets and functions between topological space called supra g-open sets and supra g-closed functions respectively, furthermore introduced the concept of supra g-open mapping and supra g-closed maps and investigated several properties of them. Additionally, we relate and compare these functions with some other functions in topological spaces.